Polyfunctional orientation of the educational process in the national pedagogy of the adyghs - Kazbek Idadovich Ashkhamakhov; Roman Sergeevich Kozlov (Вестник Майкопского государственного технологического университета, 2023)
The article considers the issues of education in Folk Pedagogy and the identification of educational technologies that contribute to the formation of the normative type of a personality within these pedagogical institutions. Problems associated with human consciousness, its opposition to the surrounding natural and social world, self-identification, self-government, etc. occupy key position in the studies of the Humanities, various approaches, judgments, concepts, claiming the role of “theoretical” laws that can consistently describe the mechanisms of human consciousness as such, the study of Folk Pedagogy, namely, the Atalyk institute among the Adyghs. To solve the problems arising from it such theoretical and methodological approaches as the analysis of historical and ethnographic literature on a given social phenomenon, methods of analogy, induction, deduction and mathematical modeling are applied. A deep comprehensive study of the studied problem can make a serious positive contribution to the scientific study of Folk Pedagogy and the Atalyk institute provide an opportunity to establish the origins, determine the factors affecting the innovative specifics of functioning in different time periods of the Adygh people, and have knowledge of its individual directions and their common system-forming interdependent unity. Patterns that will help in finding functional parameters with the resulting formal signs of existence and leading to the formation of their structural integration in the educational process have been identified. This will contribute, as we think, to the establishment of the isomorphism (sameness) of the structure of the aggregate of elements that were a part of public institutions of various types. Knowledge of its individual directions and their general system of education and upbringing.